Evaluation of Quality Parameters of Refractory Fabric with Natural Fiber - Sirojiddinova Yaxshigul Ismatillaevna; Xamraeva Sanovar Atoevna; Ahmadjonova Nozanin; Khidoyatov Omanullo Shukrullayevich (International Journal on Orange Technologies, 2022)
The article deals with the effectiveness of firefighters and to ensure their health and safety, a method of assessing the quality of flammable fabrics derived from a mixture of natural fibers, i.e. chrysotile and cotton fibers, is presented.